2022
DOI: 10.3390/foods11203217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emulsifying Salts on the Growth of Bacillus thuringiensis CFBP 3476 and Clostridium perfringens ATCC 13124 in Processed Cheese

Abstract: Processed cheese is a dairy product with multiple end-use applications, where emulsifying salts play a fundamental role in physicochemical changes during production. Moreover, some of these salts may be a strategy to control spoilage and pathogenic microorganisms, contributing to safety and shelf life extension. This study aimed to evaluate the in vitro inhibitory activity of two emulsifying salts (ESSP = short polyP and BSLP = long polyP) against Bacillus thuringiensis CFBP 3476 and Clostridium perfringens AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It is worth noting that salt treatment is an indispensable step in the commercial production of cheese, which can further discharge the internal whey and water before postripening to improve the hardness of cheese. Additionally, it can control the acidity, inhibit the growth of spoilage microorganisms that may occur during the process, and promote the maturation and flavor formation of cheese. , The involvement of Monascus spp. depends on the production requirements, and the direct inoculation into raw milk in proportion to commercial fermenters is one of the more common ways to participate in the complete process of cheese texture and flavor formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that salt treatment is an indispensable step in the commercial production of cheese, which can further discharge the internal whey and water before postripening to improve the hardness of cheese. Additionally, it can control the acidity, inhibit the growth of spoilage microorganisms that may occur during the process, and promote the maturation and flavor formation of cheese. , The involvement of Monascus spp. depends on the production requirements, and the direct inoculation into raw milk in proportion to commercial fermenters is one of the more common ways to participate in the complete process of cheese texture and flavor formation .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it can control the acidity, inhibit the growth of spoilage microorganisms that may occur during the process, and promote the maturation and flavor formation of cheese. 35,36 The involvement of Monascus spp. depends on the production requirements, and the direct inoculation into raw milk in proportion to commercial fermenters is one of the more common ways to participate in the complete process of cheese texture and flavor formation.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies (Fusieger et al . 2022a, 2022b, 2023), we evalueted the bactericidal and bacteriostatic effects of sodium polyphosphate emulsifying salts on selected targets (non‐spore‐forming bacteria and spore‐forming bacteria) in PC using both in vitro and in situ methods. It has been demonstrated that the composition of emulsifying salts plays a significant role in bacterial inhibition, and it can be influenced by interactions involving phosphates that are relevant to such inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%